Preliminary analysis of structural defects in thin BiVO4 layer using the slow-positron-beam based facilities at JINR, Dubna - Nguyen , Vu Minh Trung; Nguyen , Van Tiep; Turek, Marcin; Drozdziel, Andrzej; Pyszniak, Krzysztof; Orlov, Oleg S.; Sidorin, Alexey A.; Nguyen, La Ly; Pham , Thi Hue; Nguyen , Thi Ngoc Hue; Tran , Van Phuc; Hoang , V. Le; et al. (Nuclear Science and Technology, 2026)
The present paper introduces the slow-positron beam system at the Joint Institute for Nuclear Research (JINR). Preliminarily studies on thin films using the combined analyses of the variable energy Doppler broadening (VEDB) and variable-energy electron-momentum distribution (VEEMD) measurements at JINR are also reported. These studies provide a unique tool for the in-depth investigations of the structural defects in nanomaterial as thin films, from material’s surface to various depths (in the range from a few nm ups to 1 µm). Application of that method to BiVO4 thin film implanted with P+ ions (200 keV) reveals that the structural defects in the thin film achieve the highest concentration in the depth range of 40 – 200 nm (VEDB analysis), whereas the introduction of P+ ions into the thin film should reduce the positron annihilation probability with high-momentum core electrons. These results open the possibility to use advanced analytical techniques for in-depth study of nanomaterial in JINR, performed, in particular, by Vietnamese scientists.